Varicose veins GWAS summary statistics - Wiberg, A; Ahmed, W; Furniss, D (University of Oxford, 2022)
Summary statistics for discovery GWAS of 22,473 varicose veins cases and 379,183 non-varicose veins controls in UK Biobank. Related publication: Ahmed W. et al., Nature Communications, 2022.